Mining asteroids. - Ingebretsen, M. (IEEE spectrum)
Melting trapped ice on near Earth objects (dormant comets, asteroids) could turn a profit for private companies, with metal processing not far behind. Elaborate plans have been drawn up for NEO missions. In a typical plan, a ship departs Earth for an asteroid when the two bodies' orbits are such that the lowest change in velocity, ΔV, is required. Mining operations might last many months, and meanwhile, Earth and the NEO would be moving farther and farther apart. When the two orbits coincided once again, the mined materials could be shipped back to Earth. As with most, if not all, speculative space ventures, debate has raged over whether these missions should he manned or robotic. This paper discusses the factors that need to be considered in mining NEOs for water and the market for such water. The problems associated with such missions are also discussed